Investigation of the causes and pattern of early first permanent molar extraction in children in the western Mediterranean region of Türkiye - Zülfikar Zahit Çiftçi; Ayşe Cengiz; Büşra Buse Karamete (Contemporary Pediatric Dentistry, 2023)
Aim: This study aims to investigate the causes and pattern of extraction of first permanent molars (FPMs) in children aged 6-15 years in the western Mediterranean region of Türkiye. Methods: The data from the patients who applied to Department of Pediatric Dentistry, Faculty of Dentistry, Akdeniz University, between the years 2016–2020, were scanned; patients, who had at least one FPM extracted between the ages of 6–15, and who had pre-extraction panoramic radiographs were selected. Information about age, gender, reason for extraction, extracted tooth, and previous treatment status of a total of 562 patients (263 males and 299 females) were recorded. The data were statistically analyzed using chi-square tests. Results: The mean age was 11.87±1.89, and there was no difference between female and male patients (p=0.828). 727 FPMs were evaluated, and the main reason for extraction was detected to be “Excessive substance loss” (55.8%) for both genders in all age groups. The 2nd, 3rd, 4th, and 5th reasons were early FPM extraction, infection, parents’ request, and others respectively. The total number of extracted teeth of female patients was higher (53.6%) than that of males (46.4%) but there was no significant difference. It was observed that mandibular teeth were more frequently extracted than maxillary ones. Most children (75.8%) had one tooth extracted, 19.9% had two teeth, and 3.3% had three teeth. It was determined that the FPMs were not previously treated in the majority of children (90.7%). Conclusions: The most important finding from this study is that most of the extracted FPMs have not been treated previously. This indicates that individuals in our society do not have enough information about and are late in accessing oral health services. Therefore, further steps should be taken to improve public oral health.